2010
DOI: 10.15369/sujms.22.69
|View full text |Cite
|
Sign up to set email alerts
|

Solitary Peutz-Jeghers Type Colorectal Polyp with Hamartoma-adenoma-carcinoma Sequence in a Non-Peutz-Jeghers Syndrome Patient

Abstract: A Peutz-Jeghers P-J type polyp is a hamartomatous polyp that occurs in patients with P-J syndrome, but is rarely found as a solitary polyp in non-P-J syndrome patients 1 . There have been some reports of polyposis and cancerous transformation in patients with P-J syndrome, but few reports of solitary P-J type polyps containing cancer foci 2, 3 . We report here a rare case of a colorectal P-J type polyp showing the hamartoma-adenoma-carcinoma sequence in a non-Peutz-Jeghers syndrome patient. Case ReportA 48-yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Although it is beyond the scope of this case report to verify each possibility, Arima et al. reported a case of a colorectal Peutz‐Jeghers type polyp with hamartoma‐adenoma‐carcinoma sequence in a non‐Peutz‐Jeghers syndrome patient 10 . A disease trajectory along the hamartoma‐adenoma‐carcinoma sequence has thus been suggested to explain the cancerous transformation in hamartomatous polyps.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Although it is beyond the scope of this case report to verify each possibility, Arima et al. reported a case of a colorectal Peutz‐Jeghers type polyp with hamartoma‐adenoma‐carcinoma sequence in a non‐Peutz‐Jeghers syndrome patient 10 . A disease trajectory along the hamartoma‐adenoma‐carcinoma sequence has thus been suggested to explain the cancerous transformation in hamartomatous polyps.…”
Section: Discussionmentioning
confidence: 93%
“…Although it is beyond the scope of this case report to verify each possibility, Arima et al reported a case of a colorectal Peutz-Jeghers type polyp with hamartoma-adenoma-carcinoma sequence in a non-Peutz-Jeghers syndrome patient. 10 A disease trajectory along the hamartoma-adenoma-carcinoma sequence has thus been suggested to explain the cancerous transformation in hamartomatous polyps. In addition, the rate of CCS-related cancer was reported to be lower in patients with sustained endoscopic remission, compared to those with relapses or nonresponders.…”
Section: Discussionmentioning
confidence: 99%
“…This supported the hypothesis that both solitary Peutz–Jeghers-type polyp and PJS are associated with the risk of cancer. Arima [ 23 ] reported a case of solitary Peutz–Jeghers-type polyp with the hamartoma–adenoma–carcinoma sequence. Limaiem et al [ 24 ] reported a case of solitary rectal Peutz–Jeghers-type polyp with adenomatous transformation.…”
Section: Discussionmentioning
confidence: 99%